Effect of freezing the beef Longissimus muscle on Warner-Bratzler shear force - J.W. Homm; John A. Unruh (Kansas Agricultural Experiment Station Research Reports, 2004)
Seventy-two ribeye rolls (IMPS 112) were used to compare Warner-Bratzler shear force (WBSF) from fresh steaks and previously frozen steaks. Ribeye rolls were aged (32ºF) in vacuum-packaged bags for 14 days postmortem and fabricated into 1-inch thick longissimus muscle (ribeye) steaks. Steaks from each ribeye roll were either cooked fresh (158ºF) or stored at -20ºF before they were thawed and cooked for WBSF determination. Sensory panel determinations were also conducted on steaks stored frozen before cooking. Previously frozen steaks had lesser WBSF values (were more tender) than fresh (not previously frozen) steaks. Sensory panel attributes of myofibrillar tenderness, connective tissue amount, and overall tenderness were negatively correlated with WBSF for both fresh (r = -0.54, -0.53, and -0.58) and frozen (r = -0.63, -0.56, and -0.62) steaks, respectively. The WBSF of fresh steaks was also correlated (r = 0.48) with the WBSF of frozen steaks.
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Warner-Bratzler shear force; Longissimus; Ribeye